2019
DOI: 10.1088/1367-2630/ab3fcc
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast dynamics in the vicinity of quantum light-induced conical intersections

Abstract: Nonadiabatic effects appear due to avoided crossings or conical intersections (CIs) that are either intrinsic properties in field-free space or induced by a classical laser field in a molecule. It was demonstrated that avoided crossings in diatomics can also be created in an optical cavity. Here, the quantized radiation field mixes the nuclear and electronic degrees of freedom creating hybrid fieldmatter states called polaritons. In the present theoretical study we go further and create CIs in diatomics by mea… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
76
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 53 publications
(78 citation statements)
references
References 56 publications
2
76
0
Order By: Relevance
“…25,26 Recently, efforts have been made to study light-induced nonadiabatic phenomena in optical or microwave cavities. [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46] It has been successfully demonstrated that describing the photon-matter interaction with the tools of cavity quantum electrodynamics (cQED) [47][48][49][50] can provide an alternative way to study the quantum control of molecules with light. In this framework nonadiabatic dynamics arises due to the strong coupling between the molecular dofs and the photonic mode of the radiation eld which can alter the molecular energy levels by controlling the dynamics of basic photophysical and photochemical processes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…25,26 Recently, efforts have been made to study light-induced nonadiabatic phenomena in optical or microwave cavities. [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46] It has been successfully demonstrated that describing the photon-matter interaction with the tools of cavity quantum electrodynamics (cQED) [47][48][49][50] can provide an alternative way to study the quantum control of molecules with light. In this framework nonadiabatic dynamics arises due to the strong coupling between the molecular dofs and the photonic mode of the radiation eld which can alter the molecular energy levels by controlling the dynamics of basic photophysical and photochemical processes.…”
Section: Introductionmentioning
confidence: 99%
“…In most of the studies diatomic or polyatomic organic molecules are treated as reduced-dimensional two-level systems by taking into account only one vibrational and photonic dof. [27][28][29]34,35,42 As is already clear from classical light, quantum LICI situations can also only occur if, in addition to the only vibrational dof, the rotational angle between the molecular axis and the polarization vector of the electric eld in the cavity is also accounted for (in case of diatomics) 37,38 or at least two vibrational dofs are considered in the description. 26,44 Furthermore, quantum light-induced collective nonadiabatic phenomena (collective LICI) can also emerge when many molecules are involved in strong coupling to the cavity mode.…”
Section: Introductionmentioning
confidence: 99%
“…In such theoretical descriptions, the molecules are usually treated with a reduced number of degrees of freedom or with some simplified models assuming two-level systems [20]. However, it is worth studying single-molecule cavity interactions as well, since a more detailed study of individual objects may also provide meaningful results [22,23,[40][41][42].…”
Section: Introductionmentioning
confidence: 99%
“…The radiation field can strongly mix the vibrational, rotational, and electronic degrees of freedom, thus creating light-induced avoided crossings (LIACs) or light-induced conical intersections (LICIs) between polaritonic potential-energy surfaces [43]. Recent works discussed how the natural avoided crossings (already present in field-free systems) can be manipulated by placing the molecule into a nano-cavity and influencing the ultrafast dynamics by means of a quantized radiation field [23,42]. Field-dressed rovibronic spectra of diatomics within the framework of cavity quantum electrodynamics (CQED) have also been investigated recently [40], elucidating the significant contribution of molecular rotation to nonadiabatic effects in the spectrum.…”
Section: Introductionmentioning
confidence: 99%
“…3,22 However, limits and difficulties of few-level approximations have been pointed out, 2328 and recently, new models have been used to investigate polaritonic chemistry. 15,2841 Still, many questions remain open, especially whether the collective (ultra)strong coupling, predicted by the Dicke model can actually modify ground state properties of single molecules. 17,42 Another example is the ongoing discussion on the theoretical understanding of super-radiance.…”
mentioning
confidence: 99%